Diagnostic performance of abbreviated breast MRI for screening of women with previously treated breast cancer. Issue 16 (April 2020) - Kwon, Mi-ri; Ko, Eun Young; Han, Boo-Kyung; Ko, Eun Sook; Choi, Ji Soo; Park, Ko Woon
Abstract: Rationale and objectives: To evaluate the diagnostic performance of abbreviated screening breast magnetic resonance imaging (AB-MRI) for screening in women with previously treated breast cancer. Materials and methods: This retrospective study included consecutive AB-MRI from September 2015 to December 2016 in patients with previously treated breast cancer. Longitudinal medical record of patients' demographics, outcomes of imaging surveillance and results of biopsy was reviewed. Protocol consisted of T2-weighted scanning and dynamic contrast-enhanced imaging including one pre-contrast and two post-contrast scans. A positive examination was defined as final assessment of BI-RADS 4 or 5 and negative was defined as BI-RADS 1, 2, or 3. Abnormal interpretation rate, cancer detection rate (CDR), sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) were analyzed. Results: Among total 1043 AB-MRI, 29 (2.8%) AB-MRI had suspicious findings including 26 (2.5%) BI-RADS 4 and 3 (0.3%) BI-RADS 5 assessments. CDR was 9.59 per 1000. Performance outcomes were as follows: sensitivity, 71.4%; specificity, 98.2%; accuracy, 97.8%; PPV 1, 35.7%; PPV3 50%; and NPV 99.6%. Four cancers with false negative MRI were all early cancers of <1.0 cm with node negative. One was palpable interval cancer while the others were alternative screening modality-detected asymptomatic cancers before the next MRI screening. Conclusion: AB-MRI showed high accuracy and NPV for detecting cancer recurrence in women with previously treated breast cancer. Missed cancers were all minimal cancers with node negative.